Biofilm in cochlear implantation: our experience - Banglavuparambil, Asha A.; Muddan, Shilpa J.; Revoori, Mahesh K.; Jagini, Janardhan R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Bacterial biofilm formation on cochlear implant leads to intractable infections. Though rare, it is one of the most dreaded complications which leads to explantation in most of the cases. 400 consecutive cases of cochlear implantation done at tertiary care center over a period of 7 years included. Treatment protocol followed in Biofilm and results are discussed in our case report. Two cases of biofilm where one implant could be successfully salvaged whereas other needed explantation of the implant. There is no universally accepted standardized treatment for this complication. Salvage surgery can be attempted before explantation.